PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS HASIL PEMERIKSAAN PAJAK DAERAH PADA BADAN KEUANGAN DAERAH KOTA PONTIANAK - B2091171001, AGUS PRIYONO (MAKSI UNTAN, 2019)
This research is intended to analyse the influences of the variables-competence and independence on the result quality of regional tex inspection at Local Financial Institution in Pontianak. This research uses quantitative sources from primary and secondary data. The population in this research are 34 functional tax auditors working at Local Financial Institution in Pontianak. The sampling technique is Purposive sampling, with 34 samples. The statistical test and data processing are conducted using SPSS. The data analysis technique is descriptive statistic, and the hypothesis test uses regression analysis, test F and test T. The result of this research indicates that 1) Competence affects the inspection results of regional tax,Â  2) Independence affects the inspection results of regional tax,Â  3) Competence and Independence have effects on the inspection results of regional tax.Â Keywords : Competence, Independence, Result quality of local tax inspection.DAFTAR PUSTAKAÂ Kutipan dari Buku (1 pengarang)Adrian Sutedi. 2011. Good Corporate Governance. Jakarta: Sinar Grafika.Kutipan dari Artikel Jurnal atau Artikel MajalahÂ Â Â Â Â  Butt, J.L. 1988. Frequency Judgment in an Auditing related task. Journal of Accounting Research, 26 (Autumn), page. 315-30Choo, F. and K. T. Trotman. 1991. The Relationship Between Knowledge Structure and Judgments for Experienced and Inexperienced Auditors. The Accounting Review. JulyChristiawan, Yulius Jogi.2005. Aktivitas Pengendalian Mutu Jasa Audit Laporan Keuangan Historis. Jurnal Akuntansi & Keuangan, Vol.7, No.1, Mei 2005; 61-88.D. Frederick dan R. Libby.1990. â€œExperience and the ability to explain findings.â€ Journal of Accounting Research 28:348-367.Kutipan dari Buku (1 pengarang)Effendy. 2010. Komunikasi Teori Dan Praktek. Jakarta: PT Grasindo. RosdakaryaKutipan dari Skripsi, Thesis atau DisertasiElfarini, Eunike Christina. 2007. Pengaruh Kompetensi dan Independensi Auditor terhadap Kualitas Audit. Skripsi.Universitas Negeri Semarang.Kutipan dari Buku (1 pengarang)Ilyas, Wirawan B. 2007. Hukum Pajak, Edisi 3. Jakarta : Salemba Empat.Kutipan dari Buku (1 pengarang)Mardiasmo. 2011. â€œPerpajakan Edisi Revisiâ€. Yogyakarta:Andi.Kutipan dari Publikasi Badan (Organisasi) PemerintahStandar Profesional Akuntan Publik .2011. No. 1 tentang Standar Audit.Kutipan dari Buku (1 pengarang)Sudarmanto. 2009. Kinerja dan Pengembangan Kompetensi SDM (Teori, Dimensi Pengukuran dan Implementasi dalam Organisasi). Yogyakarta : Pustaka PelajarKutipan dari Artikel Jurnal atau Artikel MajalahÂ Â Â Â Â  Winanti, B Marliana. (2011). PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN (SURVEI PADA PT. FRISIAN FLAG INDONESIA WILAYAH JAWA BARAT). Jurnal Majalah Ilmiah UNIKOM, Vol.7, No.2 (http://jurnal.unikom.ac.id/jurnal/pengaruh-kompetensi-terhadap.24). Diakses tanggal 19-Oktober-2011.